2015
DOI: 10.1097/mco.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Myopathic characteristics in septic mechanically ventilated patients

Abstract: Many acute muscle changes in septic patients are likely to stem from pre-existing impairments, which should provide context for clinical evaluations of strength. During illness, sarcolemmal injury promotes a cascade of intra-cellular abnormalities. As unique characteristics of ICU-acquired weakness and differential effects on muscle groups are understood, early diagnosis and management should be facilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…With advances in ultrasound imaging, quantitative neuromuscular ultrasound holds the potential to evaluate nerve and muscle early in the course of disease using noninvasive means. Already, it is increasingly employed as a research outcome measure in critically ill populations 4‐7 . Recent reviews suggest that reliability of these measures has not yet been fully established, with few studies demonstrating excellent methodology when evaluated using standards developed by Guidelines for Reporting Reliability and Agreement Studies (GRRAS) and underestimated data acquired via more invasive muscle biopsy 8‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…With advances in ultrasound imaging, quantitative neuromuscular ultrasound holds the potential to evaluate nerve and muscle early in the course of disease using noninvasive means. Already, it is increasingly employed as a research outcome measure in critically ill populations 4‐7 . Recent reviews suggest that reliability of these measures has not yet been fully established, with few studies demonstrating excellent methodology when evaluated using standards developed by Guidelines for Reporting Reliability and Agreement Studies (GRRAS) and underestimated data acquired via more invasive muscle biopsy 8‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the above risk factors leading to children’s gross motor developmental dysfunction may have three pathways: 1. Prolonged mechanical ventilation and sepsis can lead to limb muscle atrophy [43, 44], resulting in weakened muscle strength in children; thus, abnormal assessment results may be due to weakened muscle strength; 2. Studies have confirmed that sepsis and IMV can cause brain dysfunction [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the above risk factors leading to children's gross motor developmental dysfunction may have three pathways: 1. Prolonged mechanical ventilation and sepsis can lead to limb muscle atrophy [42,43] , resulting in weakened muscle strength in children; thus, abnormal assessment results may be due to weakened muscle strength; 2. Studies have confirmed that sepsis and IMV can cause brain dysfunction [44,45] .…”
Section: Discussionmentioning
confidence: 99%